MAKNA PARTIKEL DE DAN TERJEMAHANYA DALAM BAHASA INDONESIA - Pragasmara, Asepta (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2013)
The particle in hinshi bunrui is called joshi. Joshi is fuzokugo that can not stand lonely, but if we put other word joshi has function as conjuntion, limitation, show the ekspression and show the word relation each other. The reason why the writer do the analysis of the particle is many particle that used in Japanese Language Gramatical instead, the function of de particle is variously. The purpose of this research is to know what and how to use de particle in Japanese Language Sentence and to find out the word translation that fit in Indonesian Language. The method that used is Padan method and devided in to three steps, they are : collecting the data, data analysis, and the last is serving the result of analysis that called conclusions. The resource of data that used is from many book, such as : Gramatika Bahasa Jepang Modern, Nihongo no Joshi, Bunkei Ziten, Nihongo no bunpo, and Gaikokujin no Tame no Joshi-Sono Oshiekata to Oboekata. De particle has six functions, they are : (1) the function of basho (to show the place to do activity), (2) the function of gentei (to show the limitation), (3) the function of zairyou (to show the main material), (4) the function of shudan (to show the tool), (5) the function of gen'in (to show the reason/ causion), and (6) the function of shutai wo arawasu hataraki (to show the main/ subject of sentence). From the result of research can made the conclusion that from the four functions just the function of shutai wo arawasu hataraki that has not translation that fit in Indonesian Language. Keywords : De Particle, Joshi De.